Manajemen Pondok Pesantren dalam Mengembangkan Mutu Baca Kitab Kuning Santri Pondok Pesantren Mambaul Ulum Bata-Bata Putri Pamekasan - Jufaini; Abdul Haq AS (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2024)
Islamic boarding schools are closely related to the study of the yellowIslamic classic book. and one of the problems that occur in pesantren is the weakness of santri in reading the yellowIslamic classic book. In an effort to develop the ability to read the yellowclassical books of the students, the Bata-bata Islamic boarding school formed an internal pesantren organization, namely M2KD (Majelis Musyawarah Kutubuddiniyah) which oversees several autonomous fields with a course system that specifically explores the yellowclassical books with educational management that has been arranged optimally to develop the ability of students in the field of kutubiyah (kutub as-Salaf). This study aims to determine the management process of Islamic boarding schools in developing the quality of reading the yellow book of students, as well as the supporting and inhibiting factors in the process of developing the quality of reading the yellow book of students at the Mambaul Ulum Bata-bata Putri Islamic Boarding School. This research uses a qualitative method with a case study approach. Data collection was carried out using in-depth interview techniques, observation and documentation. The data analysis used is an interactive analysis of the Miles and Huberman model with three stages, namely data collection, data condensation and conclusion drawing. Test the validity of the data using triangulation techniques. The results showed that the management of the boarding school in an effort to develop the quality of yellow book reading of students was carried out by forming an internal pesantren organization, namely the kutubuddiniyah deliberation assembly which oversees thirteen institutions that have different study focuses to accommodate the talents and interests of students in the field of yellow book with a fast method of group learning system to maximize the results that have been formulated. The supporting factor for this activity is the leeway from the pesantren for M2KD autonomous participants to participate in M2KD internal activities even though it conflicts with pesantren activities. The inhibiting factor is the double job of the supervisor who is felt to be less than optimal in carrying out KBM and guiding students outside KBM such as sorogan activities.